PENGARUH PEMBIASAAN BELAJAR TERHADAP TINGKAT PENCAPAIAN TUGAS-TUGAS PERKEMBANGAN SISWA SMA - Nurhidayah, Rizka; Soeharto, Soeharto; Wiyanti, Sri (Universitas Sebelas Maret, 2017)
The objective of this research were to find out: (1) the achievement level of the students? developmental tasks; (2) learning habituation guided by parents to children; and (3) the contribution of learning habituation guided by parents to the achievement level of developmental tasks of the eleventh-grade Senior High School students. The result of the analysis use One Tail Test indicated that the achievement level of developmental tasks of the eleventh-grade students of Senior High School in Surakarta and learning habituation guided by parents to that students belong to the medium category. While, the result of the analysis use simple regression indicated that learning habituation guided by parents contributed 4,8% to the achievement level of the developmental tasks.